The Benefits Of Bicycling In Minnesota - Barnes, Gary (My University, 2004)
This report establishes basic facts about bicycling in Minnesota, and estimates the sizes of the various types of benefits that bicycling creates. There are three main parts to the report. The first uses surveys and data analysis to estimate the amount of bicycling that takes place in Minnesota, and to describe its characteristics. The second part is the development of a theoretical and accounting framework for categorizing and measuring benefits. The third part calculates estimates of the total general benefits of bicycling in Minnesota. Probably about half of adults bicycle at least once in a typical summer. The benefits that result from this riding are large relative to expenditures on bicycle facilities; by our conservative assumptions, total benefits in Minnesota are in excess of $300 million per year. The size of these benefits is particularly notable when one considers that they are derived from relatively limited bicycling by most of the population. We find that the benefits to cyclists themselves are much larger than the benefits to society that bicycling creates, and that recreational riding, due to its much larger volume, creates more total benefits than does utilitarian riding.
Keywords: Bicycling